2022
DOI: 10.3390/antiox12010014
|View full text |Cite
|
Sign up to set email alerts
|

CoQ Regulates Brown Adipose Tissue Respiration and Uncoupling Protein 1 Expression

Abstract: Coenzyme Q (CoQ, aka ubiquinone) is a key component of the mitochondrial electron transport chain (ETC) and membrane-incorporated antioxidant. CoQ10 deficiencies encompass a heterogeneous spectrum of clinical phenotypes and can be caused by hereditary mutations in the biosynthesis pathway or result from pharmacological interventions such as HMG-CoA Reductase inhibitors, and statins, which are widely used to treat hypercholesterolemia and prevent cardiovascular disease. How CoQ deficiency affects individual tis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 50 publications
1
8
0
Order By: Relevance
“…Therefore, understanding the molecular mechanisms behind these events is essential to evaluate the physiological significance and potential therapeutic implications of brown adipose tissues in metabolic disorders and obesity-related conditions. Many studies using mouse models and brown adipogenesis suggest that they could be utilized to develop a new potential therapy by regulating adipose tissue browning and thermogenic activity [ 9 , 38 , 39 ]. In this study, we generated immortalized brown preadipocytes isolated from the interscapular BAT of Ucp1-luciferase transgenic mice and performed gene expression analysis during brown adipogenesis in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, understanding the molecular mechanisms behind these events is essential to evaluate the physiological significance and potential therapeutic implications of brown adipose tissues in metabolic disorders and obesity-related conditions. Many studies using mouse models and brown adipogenesis suggest that they could be utilized to develop a new potential therapy by regulating adipose tissue browning and thermogenic activity [ 9 , 38 , 39 ]. In this study, we generated immortalized brown preadipocytes isolated from the interscapular BAT of Ucp1-luciferase transgenic mice and performed gene expression analysis during brown adipogenesis in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…[1] Recent studies have highlighted CoQ10's importance in maintaining the adaptive thermogenesis and the normal morphology and physiology of brown adipose tissue, which also shows promise in ameliorating glucolipid dysmetabolism and obesity. [2][3][4] Our previous study also demonstrated that CoQ10 improved obesity and metabolic disorders induced by a high-fat diet in mice (Figures S1 and S2, Supporting Information). However, the mechanism by which CoQ10 exerts its beneficial effects is not clear.…”
Section: Introductionmentioning
confidence: 97%
“…We previously showed that BAT CoQ uptake hinges on the scavenger receptor CD36, revealing that the absence of CD36 leads to cold-intolerance (Anderson et al, 2015 ), emphasizing the significance of CoQ in BAT and thermogenesis. We also uncovered an unexpected role for CoQ in the transcriptional regulation of pivotal thermogenic genes like UCP1, affecting uncoupled respiration and leading to a rise in the inner mitochondrial membrane potential and a decline in ADP/ATP ratios (Chang et al, 2022 ). These insights prompted us to delve deeper into the effects of CoQ deficiency in BAT.…”
Section: Introductionmentioning
confidence: 99%
“…We previously found that CoQ deficiency in brown adipose tissue resulted in lower oxygen consumption rates due to suppression of uncoupling protein 1 (UCP1) expression (Chang et al, 2022 ). To further define the transcriptional signature of CoQ deficiency, we performed RNA sequencing (RNAseq) analysis of mature brown adipocytes treated with 4-chlorobenzoic acid (4CBA), a polyprenyl-diphosphate:4-HB transferase (COQ2) inhibitor to block CoQ biosynthesis, or vehicle for 24 h. Analysis of the predicted subcellular locations of the top 50 upregulated and top 50 downregulated genes revealed that 4CBA treatment affected proteins in multiple organelles.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation